PARADOKS TRITUNGGAL:: SEBUAH TINJAUAN LOGIS TENTANG TIGA DALAM SATU - Munthe, Denyka; Sumampouw, Alexander (Jurnal Teologi RAI, 2025)
The doctrine of the Trinity is one of the most fundamental teachings in Christianity, but also the most difficult to understand rationally. How can the One God be simultaneously three persons: Father, Son, and Holy Spirit? This question has been a long debate, both among philosophers, theologians, and critics of other religions. At first glance, this concept seems to contradict the law of non-contradiction in classical logic, which states that something cannot be "one" and "three" in the same sense and at the same time. However, is it true that the doctrine of the Trinity violates the principle of rationality, or is there another way to understand this concept logically? This article examines the Trinity from a theological and philosophical perspective, exploring the various approaches used to explain how three divine persons remain in one and the same essence without losing their uniqueness. By analyzing models of thought such as the Social Trinity, the Latin Trinity, and contemporary analytical approaches, this journal attempts to show that the doctrine of the Trinity is not just an irrational dogma, but has a strong rational basis. A correct understanding of the Trinity is not only relevant in academic discussions, but also plays an important role in growing faith, strengthening belief in the true God, and shaping spiritual growth based on sound teaching.